OS JUDEUS VERMELHOS (Revista de História Regional, 2007)
This article investigates the subject of the progressist Jews in Curitiba, Brazil. The research makes the connection between Jews and communism in the beginning of the 20th century. It observes the national and the cultural factors in the formation of this group. The Communist Party in Russia didnt accept thisway. The Zionist and the others Jewish groups disagreed with the progressist Jews. In Curitiba, they were ejected from the Jewish community and start a short period of autonomy. Their ssociation called SOCIB and the history of this progressist group were very productive in the cultural sense. They had theater group and s Choral of Jewish music. They tried to conserve the Jewish cultureand the Idish (dialect of the oriental Europe Jews). They had political positions very similar to the communist but tried to be autonomous and never affiliated in the party. There was others progressist groups in Brazil and also in Latin America and they had an international association called IKUF.